Eﬀect of soil and soilless media on biochemical composition of lettuce (Lactuca sativa) cultivars under open condition - Thushal R Y; Awani Kumar Singh; Gograj Singh Jat; Jeetendra Kumar Ranjan; Ram Asrey; Gyan Prakash Mishra (Current Horticulture, 2025)
A study was carried out at the Centre for Protected Cultivation and Technology (CPCT), ICAR- IARI, New Delhi, during 2022-23 to ﬁnd out the eﬀect of soil and soilless media on agro-morphological characters, yield, and economics of lettuce (Lactuca sativa L.) varieties in open conditions. The experiment was set up in a factorial randomized block design with 3 replications. Various biochemical traits including total soluble solids (5.31 ⁰Brix), antioxidant activities (40.99 DPPH inhibition %), respiration rate (2.88 ml CO2/kg/h), moisture content (83.98 %), chlorophyll content (3.05 mg/g FW), total carotenoid content (1.10 mg/g FW) and ascorbic acid content (16.55 mg/100g) of diﬀerent lettuce genotypes were higher in soil media compared to soilless media (cocopeat). Thus, it can be inferred that soil serves as a suitable medium for cultivation of lettuce varieties.